Foreword - Nina GOLOB (Acta Linguistica Asiatica, 2017)
The first, summer issue of the seventh volume of the ALA journal comprises six academic articles, of which the first three share pragmatic concepts in discourse analysis in Japanese and Bangla, while the latter three deploy different language varieties of Japanese and Chinese to provide overviews of their linguistic characteristics. Shinichi SHOJI is the author of the first article “Understanding Reference: Morphological Marking in Japanese”, which investigated the anaphor-antecedent relationship in Japanese, particularly in cases with repeated-name anaphors. He has come to the conclusion that the topic postposition wa after an anaphora determines the anaphors’ topic-hood and as such plays an important role in facilitates the realization of antecedents. Another conversational discourse was used by Soumya Sankar GHOSH, Samir KARMAKAR and Arka BANERJEE to explore the occurance and role of indeclinable ar in Bangla. Authors point out that multiple interpretations of ar, which in addition have a large semantic and pragmatic scope, can be systematized by the use of phonological context. Hironori NISHI in his article was interested in the use of the Japanese past form n deshita/n datta in a discourse. His results, based on the analyses of a large corpus, show that approximately two-thirds of the n deshita/n datta cases are not grammatically constrained, and that those cases exhibit either the speaker’s recollection of previously held knowledge, or confirmation-seeking utterances for their previously held knowledge. Andrei A. AVRAM explored phonological, morphological, syntactic and lexical aspects of Yokohama Pidgin Japanese and Japanese Pidgin English to find out that the bi-directional approach detected several common features typical of pre-pidgins though the two languages differ considerably in the circumstances of their emergence and the context of use. Yet another language variety, namely the legal Chinese sociolect, was analyzed quantitatively by Ľuboš GAJDOŠ. Referring to the Chinese monolingual corpus Hanku, the author touched several statistical parameters, including the length of sentences and the proportion of parts of speech, and additionally discussed the issues on statistical data processing.